Transcultural validation of an instrument to evaluate Advanced Nursing Practice competences in Brazil - Kamila Caroline Minosso; Beatriz Rosana Gonçalves de Oliveira Toso
ABSTRACT Objectives: to carry out a transcultural validation of the Modified Advanced Practice Nursing Role Delineation Tool for the Brazilian language. Methods: methodological and quantitative study, including the process of translation and cultural adaptation of the instrument. The committee of evaluators was formed by seven experts. Data collection for the pre-test took place from November 2020 to January 2021, with 30 nurses from the West of Paraná. Data analysis used Cronbach's alpha, intraclass correlation, and kappa. Results: the agreement of the evaluator committee reached a substantial kappa of 0.68 and an intraclass correlation of 0.80, and as a result, the version for application in a pretest was approved. The pretest found a 0.98 Cronbach's Alpha and an intraclass correlation of 0.61. Conclusions: the instrument was found to be culturally adapted and can be used in the country to identify the competences of the Primary Healthcare Nurses to develop advanced nursing practices.